Position-Dependent Influence of the Three Trp Residues on the Membrane Activity of the Antimicrobial Peptide, Tritrpticin - Mauricio Arias; Leonard T. Nguyen; Andrea M. Kuczynski; Tore Lejon; Hans J. Vogel (MDPI AG, 2014)
Antimicrobial peptides (AMPs) constitute promising candidates for the development of new antibiotics. Among the ever-expanding family of AMPs, tritrpticin has strong antimicrobial activity against a broad range of pathogens. This 13-residue peptide has an unusual amino acid sequence that is almost symmetrical and features three central Trp residues with two Arg residues near each end of the peptide. In this work, the role of the three sequential Trp residues in tritrpticin was studied in a systematic fashion by making a series of synthetic peptides with single-, double- and triple-Trp substitutions to Tyr or Ala. 1H NMR and fluorescence spectroscopy demonstrated the ability of all of the tritrpticin-analog peptides to interact with negatively-charged membranes. Consequently, most tritrpticin analogs exhibited the ability to permeabilize synthetic ePC:ePG (egg-yolk phosphatidylcholine (ePC), egg-yolk phosphatidylglycerol (ePG)) vesicles and live Escherichia coli bacteria. The membrane perturbation characteristics were highly dependent on the location of the Trp residue substitution, with Trp6 being the most important residue and Trp8 the least. The membrane permeabilization activity of the peptides in synthetic and biological membranes was directly correlated with the antimicrobial potency of the peptides against E. coli. These results contribute to the understanding of the role of each of the three Trp residues to the antimicrobial activity of tritrpticin.